Immune composition of the mononuclear cell fraction of human umbilical cord blood - Kikuta, Karen; Lee, Esmond; Menezes, Talia; Fung, Hannah; Amorin, Alvaro; Agrawal, Aditi; Roth, Theodore L.; Porteus, Matthew (Frontiers in Immunology, 2025)
Despite its therapeutic potential and unique immunological properties, the immune composition of umbilical cord blood lacks consistent and comprehensive characterizations. Human umbilical cord blood (UCB) is often discarded after delivery and is difficult to obtain for research purposes. Furthermore, most research on UCB is focused on properties of CD34+ hematopoietic stem cells for transplantation. The Binns Program for Cord Blood Research at Stanford University has the unique advantage of regular collection and isolation of mononuclear cells (MNC) from UCB donors. This study provides a robust characterization of the immune subset compositions of the CD34-negative MNC fraction of UCB (n=50). The study also compares the UCB data to adult peripheral blood (PB) mononuclear cells to identify differences in immune maturity. Using flow cytometry and single-cell RNA sequencing (scRNA-Seq), we analyzed UCB and adult PB MNC samples to characterize the cell surface protein and transcriptomic profiles of different immune subsets. Our study findings bring a higher-definition understanding of the unique immunological properties of umbilical cord blood. Study findings reveal a distinct immune profile in UCB, such as a higher average percentage of CD19 B Lymphocytes, CD4 T Cells, CD4 Naive T Cells, CD4 Recent Thymic Emigrants, CD8 Naive T Cells, CD8 Recent Thymic Emigrants, and CD19 Naive B Cells compared to adult PB. Additionally, there were fewer CD19 Memory B Cells in UCB compared to PB. The scRNA-Seq showed concordance in the proportion of immune cell types but captured more differentiated subtypes of cells. Additionally, scRNA-Seq showed unique clustering patterns in UCB, which reflect cell types that converge in adulthood as the immune system matures. These analyses yield the intriguing possibility that the immune heterogeneity of individuals at birth gives way to more stereotyped immune subsets as the immune system is exposed to the external environment and undergoes maturation. Overall, our findings provide a robust characterization of MNC UCB immune subsets and insights into how immune function develops from birth to adulthood.